2015
DOI: 10.4209/aaqr.2015.04.0271
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine Particles and PM2.5 at Three Urban Air Monitoring Stations in Northern Taiwan from 2011 to 2013

Abstract: In this study, long term measurements of PM 2.5 and ultrafine particles (UFPs) for daily average mass concentration at Zhongshan (ZS), Sinjhuang (SJ), and Jhudong (JD) urban air monitoring stations were conducted from 2011 spring to 2013 autumn. The results showed that daily average UFPs mass concentrations in spring (average at 3 stations: 1.58 ± 0.74 µg m -3 ) and summer (average at 3 stations: 1.59 ± 0.53 µg m -3 ) were higher than those in autumn (average at 3 stations: 1.02 ± 0.28 µg m -3 ) and winter (av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Previous study (Lin et al, 2015) in other megacities reported that 𝜒 of all particles was around 2 with Da at around 100 nm which is close to our results. Previous measurements (Zhang et al, 2016) transform to be more spherical-like by acquiring more secondary species (Ahern et al, 2016).…”
Section: Size-resolved Particle Morphologysupporting
confidence: 93%
“…Previous study (Lin et al, 2015) in other megacities reported that 𝜒 of all particles was around 2 with Da at around 100 nm which is close to our results. Previous measurements (Zhang et al, 2016) transform to be more spherical-like by acquiring more secondary species (Ahern et al, 2016).…”
Section: Size-resolved Particle Morphologysupporting
confidence: 93%
“…It was justified by the need to separate local pollution sources, such as traffic, heating, or industrial emissions, which are also capable of generating nano-sized particles. Local pollution sources are very pertinent in a city, because vehicles generate large amounts of ultrafine particles (Wahlin et al, 2001;Gidhagen et al, 2005;Monkkönen et al, 2005;Lin et al, 2015) all over the city. Heating and industrial sources also generate large amounts of ultrafine particles.…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2014;Liu C.N. et al, 2015) and ultrafine particles (Chen S.C. et al, 2010a;Chen S.C. et al, 2010b), long-term measurement for PM 2.5 and ultrafine particles mass concentrations (Lin G.Y. et al, 2015), and the measurement of PM 10 , PM 2.5 and PM 0.1 for source characterization and apportionment (Gugamsetty B. et al, 2012).…”
Section: Application Of Inertial Impactorsmentioning
confidence: 99%
“…To determine the compliance with NAAQS, it is often desirable to fractionate particles into two size fractions simultaneously, one corresponding to the coarse particle mode (> 2.5 μm) and one corresponding to the fine particle mode (≤ 2.5 μm). The virtual impactor is very suitable for this application (Lin G.Y. et al, 2015;Landis M.S.…”
Section: The Inlet For Two Size Fractionsmentioning
confidence: 99%